A phylogenetic framework for the bumblebee species of the subgenus Bombus sensu stricto based on mitochondrial DNA markers, with a short description of the neglected taxon B. minshanicola Bischoff, 1936 n. status. (Hymenoptera: Apidae: Bombus). - Bertsch, Andreas (Contributions to Entomology = Beiträge zur Entomologie, 2010)
Queens of 12 taxa of the subgenus Bombus sensu stricto (Bombus affinis, B. albocinctus, B. cryptarum, B. lucorum, B. magnus, B. moderatus, B. occidentalis, B. patagiatus, B. sporadicus, B. terrestris, B. terricola and B. tunicatus) were collected in spring to establish artificial colonies. Males of B. franklini and B. lucorum/China were also collected. Mitochondrial cytochrome oxidase subunit I (COI) was sequenced from 53 specimens (partial sequence length 1257 bp). GenBank sequences of the east Asiatic species B. hypocrita and B. ignitus were included in the investigation. The interspecific sequence diversity was about 30–92 base substitutions with a Tamura-Nei genetic distance of 0.030 – 0.103, whereas the intraspecific sequence diversity was only 1–3 base substitutions with a Tamura-Nei genetic distance of 0.001–0.003. Thirteen Taxa ranked as species were found and a new taxon ranked as species B. minshanicola Bischoff 1936 (= B. terrestris ssp. minshanicola = B. lucorum /China) was established. Four clusters were obtained in the topology of the phylogenetic tree: a species pair B. ignitus – B. sporadicus, a species pair B. terricola – B. occidentalis, a cluster including B. magnus, B. patagiatus and B. cryptarum with ssp. B. cryptarum albocinctus and B. cryptarum moderatus, and a cluster including B. hypocrita, B. lucorum, B. minshanicola, B. franklini and B. affinis. The species B. terrestris with ssp. B. terrestris canariensis and B. terrestris sassaricus and B. tunicatus were well separated. As there are no gaps in the alignment of the COI sequences, single nucleotide sites can be used as positional homologies. Each taxon is characterized by substitutions that are unique and can be used as diagnostic characters to define and identify the taxon.